2017
DOI: 10.1681/asn.2016121272
|View full text |Cite
|
Sign up to set email alerts
|

IL233, A Novel IL-2 and IL-33 Hybrid Cytokine, Ameliorates Renal Injury

Abstract: CD4Foxp3 regulatory T cells (Tregs) protect the kidney during AKI. We previously found that IL-2, which is critical for Treg homeostasis, upregulates the IL-33 receptor (ST2) on CD4 T cells, thus we hypothesized that IL-2 and IL-33 cooperate to enhance Treg function. We found that a major subset of Tregs in mice express ST2, and coinjection of IL-2 and IL-33 increased the number of Tregs in lymphoid organs and protected mice from ischemia-reperfusion injury (IRI) more efficiently than either cytokine alone. Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(116 citation statements)
references
References 62 publications
4
111
0
1
Order By: Relevance
“…Administration of anti‐CD28 superagonist antibody was shown to increase Tregs and protect from AKI in a mice model, but phase I studies in healthy volunteers showed unexpected life‐threatening adverse effects with this drug . Very recently, treatment of mice with a hybrid cytokine (IL‐233, that bears the activities of IL‐2 and IL‐33) increased Treg mediated protection from AKI . Clinical studies are awaited.…”
Section: Cellular and Molecular Factors Associated With Renal Regenermentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of anti‐CD28 superagonist antibody was shown to increase Tregs and protect from AKI in a mice model, but phase I studies in healthy volunteers showed unexpected life‐threatening adverse effects with this drug . Very recently, treatment of mice with a hybrid cytokine (IL‐233, that bears the activities of IL‐2 and IL‐33) increased Treg mediated protection from AKI . Clinical studies are awaited.…”
Section: Cellular and Molecular Factors Associated With Renal Regenermentioning
confidence: 99%
“…90,91 Very recently, treatment of mice with a hybrid cytokine (IL-233, that bears the activities of IL-2 and IL-33) increased Treg mediated protection from AKI. 92 Clinical studies are awaited.…”
Section: Initial Pro-inflammatory Responsementioning
confidence: 99%
“…Intriguingly, a beneficial function of IL-33 has also recently been reported in a study that developed a hybrid IL-2-IL-33 fusion; researchers observed a protective role for the fusion protein in kidney IRI models, mediated via the expansion of renal ILC2s [54]. Short-term treatment with IL-33 also leads to the sustained expansion of renal ILC2s and protects against adriamycin-induced glomerulosclerosis [55].…”
Section: Kidney Diseasesmentioning
confidence: 69%
“…80 As IL-2 and IL-33 promote the expansion of murine Tregs in vivo, Stremska et al generated an IL-2 and IL-33 fusion cytokine that they termed IL-233, and which they found increased the recruitment of Tregs into the kidney and protected mice from IRI more efficiently than either cytokine alone. 81 Thus, these studies collectively suggest that strategies aimed at enhancing numbers, recruitment and function of endogenous Tregs demonstrates therapeutic potential in AKI, especially as therapies prior to injury in situations where AKI is likely or probable.…”
Section: Ischaemia-reperfusion Injurymentioning
confidence: 95%
“…The renoprotective effects of human‐umbilical cord blood‐derived MSCs administered early after cisplatin administration are potentially via Tregs . As in IRI, the hybrid cytokine IL‐233 protected mice from cisplatin‐induced AKI, but whether this was mediated through increased recruitment of Tregs to the kidney (as in IRI) was not determined . Given that patients with solid organ tumours are given cisplatin in a known timeframe, IL‐233 as well as PLA2 and MSCs, assuming they do not limit the anticancer effects of cisplatin may have therapeutic potential.…”
Section: Acute Kidney Injurymentioning
confidence: 99%